Platelet secretion from dense and alpha-granules in vitro in migraine with or without aura. Issue 5 (May 1994) - D'Andrea, G; Hasselmark, L; Alecci, M; Cananzi, A; Perini, F; Welch, K M
Abstract : Several studies in vivo indicate platelet activation in migraine, as reflected by increased plasma concentrations of platelet secretory products. In vitro data on platelet secretion are scant, which prompted an investigation into agonist-induced platelet aggregation and secretion in platelets from patients with migraine. Sixty two patients with migraine with aura (MA) and 41 with migraine without aura (MwA) were studied during a headache-free phase, together with 26 healthy controls. Platelet aggregation and secretion in platelet-rich plasma were induced by collagen and platelet activating factor (PAF). Serotonin was measured by high performance liquid chromatography and platelet factor 4 (PF4) with an enzyme immunoassay kit. There were no significant aberrations in platelet aggregation in those with migraine compared with healthy controls. The platelet PF4 secretion induced by PAF (1.0 and 0.1 microM) was increased in MwA (p < 0.05, p < 0.0001) compared with controls, and there was a similar trend in MA (NS, p < 0.01). By contrast, the PF4 secretion induced by collagen (0.5 and 2.0 micrograms/ml) was reduced in MA (p < 0.01 and p < 0.05). Further, the MA group exhibited increased basal intraplatelet serotonin concentrations (p < 0.0001) and increased serotonin secretion induced by both concentrations of collagen (p < 0.0001) and PAF (p < 0.001). The data indicate an abnormal platelet a-granule secretion in those with migraine, and focus attention on PAF as a possible factor contributing to the platelet activation associated with migraine. The increased platelet content and secretion of serotonin was specific to MA, and may reflect different serotonin turnover in the two clinical migraine types.